A Jamesonian analysis of "flat world" imagery in education discourse. Issue 2 (3rd March 2016) - Collin, Ross
Abstract : This article presents a discourse analysis of Kylene Beers' presidential address to the 2009 conference of the National Council of Teachers of English (NCTE-USA). The address, titled "Sailing over the Edge: Navigating the Uncharted Waters of a World Gone Flat, " calls teachers to reject the standardized education of the industrial order and to harness the creativity at the heart of the "flat world" (i.e. global, knowledge-based capitalism). The discourse analysis focuses on the figure of the "flat world" – an increasingly common image in education research – and asks how the speech uses the figure of the "flat world" to reimagine the role of education under global capitalism. Mobilizing the ideas of Fredric Jameson, the Marxist literary critic, the article asks how the speech's story of education in the "flat world" offers "an imaginary resolution of a real contradiction" between industrial and knowledge-based capitalisms.